Earliest occurrence of lophogastrid mysidacean arthropods (Crustacea, Eucopiidae) from the Anisian Luoping Biota, Yunnan Province, China. (5th December 2016) - Feldmann, Rodney M.; Schweitzer, Carrie E.; Hu, Shixue; Huang, Jinyuan; Zhou, Changyong; Zhang, Qiyue; Wen, Wen; Xie, Tao; Schram, Frederick R.; Jones, Wade T.
Abstract: Tiny, pelagic arthropods from the Anisian Luoping Biota exposed in two quarries near Luoping, Yunnan Province, China, represent the numerically most abundant organisms in the assemblage. They form the basis for definition of two, and possibly three, species referred to the order Lophogastrida, family Eucopiidae. Yunnanocopia grandis new genus new species and Y . longicauda n. gen. new species represent the oldest occurrence of mysidaceans in the fossil record. Their anatomy allies them with the Ladinian species Schimperella acanthocercus Taylor, Schram, and Shen, 2001, from Guizhou Province, China, which previously was thought to be the oldest lophogastrid, and with extant species of Eucopiidae. Their appearance in the Anisian represents one additional element of the early faunal radiation within the Luoping Biota following the end-Permian extinction event. Presence of well-preserved oostegites, along with other morphological features, documents a conservative bauplan expressed in Eucopiidae.